2021
DOI: 10.22543/7674.82.p280285
|View full text |Cite
|
Sign up to set email alerts
|

The management of tubo-ovarian abscesses associated with appendicitis

Abstract: A relatively uncommon medical complication, the tubo-ovarian abscess (TOA) can result from ascending pelvic infection in the female genital tract. The paper aims at exploring the characteristics of patients with TOA and at comparing the outcomes of the surgical management with postoperative recovery. A retrospective analysis of 25 cases diagnosed with bilateral, right or left TOA at “St. Apostol Andrei” Emergency Clinical County Hospital Constanta, Romania between January 2019 and December 2020 was performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The neurological sequels are the most prevalent amniotic fluid complications reported in observational studies, affecting between 24% and 50% of cases [6,18,19]. The neurological sequels are closely followed by renal failure [20,21], cardiovascular and pulmonary disorders [22,23], or infectious complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…The neurological sequels are the most prevalent amniotic fluid complications reported in observational studies, affecting between 24% and 50% of cases [6,18,19]. The neurological sequels are closely followed by renal failure [20,21], cardiovascular and pulmonary disorders [22,23], or infectious complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…In 50% of the patients, the appendix was involved with the TOA and thought to be the possible source of infection [ 1 ]. In another retrospective study, Serbanescu et al found that three out of 25 patients diagnosed with right and left TOA also had appendicitis and Nishida et al cited a case of a 12-year-old virginal female who developed recurrent TOAs five years after an appendectomy [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%